Experimental Analysis on Replacement of Aggregate by Broken Ceramic Tiles in Concrete A REVIEW - Abhishek Kumar Vishwakarma; Afzal Khan (International Journal of Scientific Research in Civil Engineering, 2022)
According to the introduction attempts this examination focuses on the waste clay tile total as incomplete coarse totals swap for the solid creation, the neutralizing activity of environmental pollution with considering the segments of sensible and cost-saving advancement adventures, especially material usage. In addition, huge numbers of the development enterprises in India create development squander that contributes to a great extent to strong waste. Use earthenware tile squander, this examination will concentrate on artistic squanders get from the development business in India. By and by a significant part of the fired ventures creation goes to squander, which isn't experiencing the reusing procedure yet. In this paper presenting review of past researches and publications.
Keywords: Ceramic Waste; Concrete; Mix Design; Compressive Strength; Aggregate; Flexural Strength